Formation, Development, and Propagation of a Rare Coastal Coccolithophore Bloom. Issue 5 (22nd May 2019) - Matson, Paul G.; Washburn, Libe; Fields, Erik A.; Gotschalk, Chris; Ladd, Tanika M.; Siegel, David A.; Welch, Zoë S.; Iglesias‐Rodriguez, M. Debora
Abstract: This study examines an unprecedented bloom of Emiliania huxleyi along the California coast during the NE Pacific warm anomaly of 2014–2015. Observations of coccolithophore populations from microscopy and flow cytometry, surface current data derived from high‐frequency radar, and satellite ocean color imagery were used to track the population dynamics of the bloom in the Santa Barbara Channel. Results show a coastal bloom of mostly E. huxleyi that reached cell concentrations up to 5.7 × 10 6 cells per liter and a maximum spatial extent of 1, 220 km 2 . We speculate that the rare cooccurrence of warm water, high water column stability, and an extensive preceding diatom bloom during the anomaly contributed to the development of this bloom. Flow cytometry measurements provided insight on the phases of bloom development (e.g., growth versus senescence) with calcified cells comprising up to 64% of particles containing chlorophyll a and detached‐coccolith:cell ratios ranging from 10 to >100. Lagrangian particle trajectories estimated during two nonoverlapping 48‐ and 72‐hr periods showed the changes in the surface structure of the bloom due to advection by surface currents and nonconservative biological and physical processes. Time rates of change of particulate inorganic carbon were estimated along particle trajectories, with rates ranging from −4 to 6 μmol·L −1 ·day −1 . The approach presented here is likely to be useful for understanding the evolution of coastal phytoplankton bloom events in a general setting. Plain Language Summary: This study examines an unprecedented bloom of the coccolithophore Emiliania huxleyi, a single‐celled algae that is covered by calcium carbonate plates, along the California coast during a period of unusually warm water during 2014–2015. We used microscopy and flow cytometry, surface current data, and satellite ocean color imagery to track how the bloom changed through time in the Santa Barbara Channel. Results show a coastal bloom of mostly E. huxleyi that reached cell concentrations up to 5.7 × 10 6 cells per liter and covered up to 1, 220 km 2 . We speculate that the rare cooccurrence of environmental conditions, including warm water, high water column stability, and an extensive preceding diatom bloom during the anomaly, contributed to the development of this bloom. Flow cytometry measurements provided insight on the phases of bloom development (e.g., growth versus senescence) and hourly surface current data to simulate how currents may have moved the coccolithophores during the course of the bloom. In addition, we combined this data with satellite imagery to estimate how the amount of calcium carbonate in this bloom changed through time. The approach presented here is likely to be useful for understanding the rise and fall of phytoplankton blooms along the coast. Key Points: Unprecedented coastal bloom of the coccolithophore Emiliania huxleyi during 2014/2015 warming anomaly occurring along the California coast Lagrangian particle trajectories showed changes in bloom structure due to advection by surface currents and nonconservative processes Bloom phases identified based on particle trajectories and satellite‐derived estimates of change in particulate inorganic carbon